Identification of Enterococcus faecalis Isolated from Infected Human Tooth Root Canals Human by Using Polymerase Chain Reaction - Hasson, Athraa H.; Kadhem, Susan A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
One hundred samples of root canal bacteria were isolated from patients teeth with primary and secondary infected root canal from all the ages . Biochemical and microscopial tests were done for identification of these isolates. Twenty four isolates were confirmed as E. faecalis species by using these tests. Genetic diagnosis for the all isolates was also done by using polymerase chain reaction ( PCR ). Thirty two isolates were confirmed to belong to E. faecalis species by using this test.